2010
DOI: 10.1029/2010gl043556
|View full text |Cite
|
Sign up to set email alerts
|

Role of vertical migration in biogenic ocean mixing

Abstract: [1] Recent efforts to empirically measure and numerically simulate biogenic ocean mixing have consistently observed low mixing efficiency. This suggests that the buoyancy flux achieved by swimming animals in the ocean may be negligible in spite of the observed large kinetic energy dissipation rates. The present letter suggests that vertical migration across isopycnals may be necessary in order to generate overturning and subsequent mixing at length scales significantly larger than the individual animals. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 18 publications
1
36
1
Order By: Relevance
“…Experiments have confirmed these effects, and can now describe the flows produced by microorganisms in detail [11][12][13]. Larger organisms (such as krill) may have a significant effect on the flow at high Reynolds numbers, and it has been suggested that their activity may produce a non-negligible contribution the ocean kinetic energy budget [14][15][16]. Comparatively little work, however, has been done to understand the effects of nontrivial flow fields on swimming particles, even though the coupling between the fluid flow and the particle dynamics may lead to qualitatively new behavior.…”
mentioning
confidence: 67%
“…Experiments have confirmed these effects, and can now describe the flows produced by microorganisms in detail [11][12][13]. Larger organisms (such as krill) may have a significant effect on the flow at high Reynolds numbers, and it has been suggested that their activity may produce a non-negligible contribution the ocean kinetic energy budget [14][15][16]. Comparatively little work, however, has been done to understand the effects of nontrivial flow fields on swimming particles, even though the coupling between the fluid flow and the particle dynamics may lead to qualitatively new behavior.…”
mentioning
confidence: 67%
“…However, vertical migration across isopycnals may be necessary in order to generate mixing at length scales significantly larger than K. Katija individual animals. In a theoretical study of passive spheres moving in linearly stratified potential flow, as the number of bodies increased (and their relative position became more staggered), the vertical displacement of fluid parcels became much larger than individual body sizes (Dabiri, 2010). These simulations show that schooling animals during vertical migration through stratified fluid have the ability to generate mixing at scales larger than the individual animal.…”
Section: Models For Understanding Multi-animal Fluid Transportmentioning
confidence: 89%
“…A swimming animal can generate turbulence at scales of the same order as their body size; smaller animals (residing in low-Re, viscous fluid regimes) are incapable of generating larger, more energetic eddies such as those produced by pelagic fish and whales. Although there are claims that schooling of small animals effectively increase the scales of turbulence to scales characterizing the school (Huntley and Zhou, 2004;Kunze et al, 2006;Dabiri, 2010), the mechanisms that would allow for this conversion is not well understood. However, with the identification of drift, a mixing mechanism that is applicable to any moving body regardless of size or shape, smaller animals can generate efficient mixing as well (Katija and Dabiri, 2009).…”
Section: Identifying Potential Biogenic Mixersmentioning
confidence: 99%
“…17,18 Furthermore, a simplified model of multiple swimming animals suggests that vertical transport in a stably stratified fluid depends on the arrangement of the swimmers within the group. 19 Other factors such as the swimming mode of the organisms and the number density of animals within the aggregations are anticipated to affect fluid transport as well.…”
Section: Introductionmentioning
confidence: 99%